Postprandial changes of oxidative stress biomarkers in healthy individuals - Huang, Fengyi; Shen, Xue; Zhang, Yuzheng; Vuong, Ann M.; Yang, Shuman (Frontiers in Nutrition, 2022)
Food consumption induces oxidative stress in humans, but the changes in oxidative stress levels after a regular meal are still unclear. We conducted an experimental study on twenty healthy volunteers (10 males, 10 females), who matched in age (± 2 years). They were given a regular diet (total energy of 704 kcal, which contains 75 g of carbohydrates, 35 g of protein, and 29 g of lipids) at 11:30 a.m. after a fast of over 12 hours. We collected 6-repeated measures of venous blood samples at 2-hour intervals via heparin anticoagulant tubes immediately after the meal (indicated as “0” hour) and up to 10 hours post-consumption. Biomarkers included plasma fluorescent products, plasma malondialdehyde, plasma total antioxidant capacity, and superoxide dismutase. FlOPs were measured at three excitation/emission wavelengths (FlOP_320, FlOP_360, and FlOP_400). The average age and BMI for the eight participants were 22.70±1.98 years and 20.67 ± 2.34 kg/m2, respectively. Within 10 hours after the meal, the overall trend of FlOPs were generally similar. There was no evidence of dose response for any of the three FlOPs (all P >0.05). However, levels of MDA decreased with the time of fasting (P linear and P quadratic < 0.05), with the biggest decrease occurring between 0-2 hours post-meal. The overall trend of T-AOC and SOD levels also decreased with fasting time (P linear and P quadratic < 0.05), though an increase was observed between 0-2 hours following consumption. Levels of MDA, T-AOC, and SOD but not FlOPs, decreased with fasting time.